Mineral Chemistry and U-Pb Garnet Geochronology of Strongly Reduced Tungsten Skarns at the Pampa de Olaen Mining district, Córdoba, Argentina - Espeche, María José (2021)
Los Guindos scheelite (±Zn, Bi, Sn, Ag) skarn presents mineral assemblages and a mineral chemistry similar to other worldwide strongly reduced W skarn deposits. Its reduced nature is defined based on the predominance of subcalcic garnets, Mo-free scheelite and absence of magnetite. Both the prograde and retrograde stages are evident at Los Guindos scheelite skarn. The prograde skarn is characterized by three zones: A zone I of garnet + helvine (Gr57Sps24Ad19Alm8 - Sps50Alm24Gr22Ad3; Grt + Hlv); a zone II of clinopyroxene + garnet (Di67Hd24Jo9 + Gr66Sps19Ad12Alm3; Cpx + Grt) and a zone III of garnet + vesuvianite (Gr73Ad22Sps3Alm2 - Gr58Sps22Ad10Alm9; Grt + Ves). Retrograde skarn is mainly represented by epidote - actinolite and minor F-rich actinolite (0.663 apfu of F) – potassium feldspar - chlorite (chamosite/clinochlore: ∼ 50/50) – muscovite – calcite - quartz. A hydrothermal stage developed in temporal continuity with retrograde skarn formed variable infilling associations of the following species: epidote – actinolite – scheelite – fluorite – calcite – quartz – sphalerite and chlorite. Scheelite mineralization process was triggered by an increase of Ca released during retrograde skarn replacements and was deposited during the following hydrothermal infilling stage. Other than sphalerite, minor bismuthinite and tetradymite, andorite, lillianite, gustavite, matildite and kësterite occur as hydrothermal associations after scheelite deposition. Scheelite-free reaction skarn preceding scheelite skarns was observed. Geobarometric calculations in this reaction skarn suggests an initial confining pressure of 2.5 kbar for the Los Guindos scheelite skarns. This pressure matches the estimated emplacement pressure of the Devonian-Carboniferous Achala batholith reported by previous authors. Geochemical correlation analyses suggest that this magmatism may have contributed mineralizing fluids channeled through regional structures and lithological contacts, causing infiltration metasomatism that originated scheelite (±Zn, Bi, Sn, Ag) mineralization in Cambrian and Ordovician country rocks. U-Pb analyses (LA-ICP-MS) of garnet in the Los Guindos scheelite skarn gave an age of 361 ± 11 Ma representing the age of the prograde stage of scheelite skarns and it should be framed within the Devonian-Carboniferous Metallogenic Epoch.